2021
DOI: 10.4236/pp.2021.1212028
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Antimicrobials Susceptibility Pattern of <i>Staphylococcus aureus</i> Associated with Wound Infections in Surgery Department, Wad Madani Teaching Hospital, Sudan

Abstract: Background: Most community and hospital acquired infections are due to Staphylococcus aureus, these infections involve both local suppurative and systemic conditions. There is an increase in the incidence rates of acquiring resistant strains of Staphylococcus aureus in hospitals and community in Sudan. This study aims to detect frequency of Staphylococcus aureus isolated from surgical-sites infections (SSIs) and traumatic wounds, and to determine susceptibility to commonly used drugs. Methods: Prospective cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
1
2
Order By: Relevance
“…The age groups most affected by SSTI were those between 19 and 35 years followed by those between 36 and 59 years with SSTI in the 19–59 group being more likely to be due to MDR pathogens compared to those less than 12 years. This contrasts previous studies that reported a higher likelihood of infection among those above 35 years [ 47 , 48 ]. This might be because this age group is the most active in life, prone to injuries and therefore exposure to antibiotics during treatment of the injuries, increasing their risk for MDR infections.…”
Section: Discussioncontrasting
confidence: 99%
“…The age groups most affected by SSTI were those between 19 and 35 years followed by those between 36 and 59 years with SSTI in the 19–59 group being more likely to be due to MDR pathogens compared to those less than 12 years. This contrasts previous studies that reported a higher likelihood of infection among those above 35 years [ 47 , 48 ]. This might be because this age group is the most active in life, prone to injuries and therefore exposure to antibiotics during treatment of the injuries, increasing their risk for MDR infections.…”
Section: Discussioncontrasting
confidence: 99%
“…The age groups most affected by SSTI were those between 19 and 35 years followed by those between 36 and 59 years with SSTI in the 19-59 group being more likely to be due to MDR pathogens than those less than 12 years. This contrasts previous studies that reported a higher likelihood of infection among those above 35 years (24,42). This might be because this age group is the most active in life, prone to injuries and risks that increase their probability of acquiring MDR infections.…”
Section: Discussioncontrasting
confidence: 88%
“…S. aureus is one of the main pathogens in hospitals and communities that can cause many infectious diseases, such as mild skin and soft tissue infections, infective endocarditis, osteomyelitis, bacteremia, and fatal pneumonia [10,11].…”
Section: Discussionmentioning
confidence: 99%